Epidermal Properties and Stomatal Abnormalities of two Amaryllidaceae Taxa (Crinum album and Scadoxus multiflorus) Growing in Yemen and their Taxonomic Significance - Alhadi, Fatima A.; Al-matri, Shaima’a A. N.; Ibrahim, Hassan M. (PSM Biological Research, 2025)
This study investigated the epidermal properties and Stomatal abnormalities of two Amaryllidaceae taxa (Crinum album and Scadoxus multiflorus) and their taxonomic significance. Our analysis revealed twelve quantitative properties out of a total of 53 (17 qualitative and 36 quantitative) studied properties, which showed significant differences between C. album and S. multiflorus. These properties includes eight quantitative properties observed on both the adaxial and abaxial surfaces (Number of epidermal cells per ×250 field of view, Width of epidermal cells, Size of the epidermal cells, Wall thickness of the epidermal cells, Number of stomata per ×250 view, Stomata Index, Guard cells area and the Size of stomata), two quantitative properties specific to the adaxial surface (Size of epidermal cell, and Guard cell width), and two quantitative properties particular to the abaxial surface (Percentage of Tetracytic stomata and Guard cell length). Moreover, the 53 epidermal characters (17 qualitative and 36 quantitative) were subjected to numerical analysis using Two-way cluster analysis (TWCA), and the resulting dendrogram showed that the relative similarity level between C. album and S. multiflorus is about 87.92%.